1998
DOI: 10.1007/s001250050862
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycaemia modifies the reaction of microvessels to insulin in rat skeletal muscle

Abstract: Glucose homeostasis is partly due to the metabolic action of insulin, which exerts its antihyperglycaemic action mainly in liver, adipose tissue and skeletal muscle. In the basal state, skeletal muscle utilizes little glucose as a fuel for its own needs [1]. In contrast, during postprandial periods the disposal of glucose is partly insulin-mediated and occurs mainly in skeletal muscle [2], where it is largely stored as glycogen. At this time, skeletal muscle switches from a low glucose-consuming to a major car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
1

Year Published

2000
2000
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 54 publications
2
56
1
Order By: Relevance
“…One has looked at the chronological evolution of the process in insulin-resistant, fructose-fed rats and found that they were first insulin resistant, then endothelium-dependent vasodilatation defects appeared and finally hypertension developed [14]. Precapillary vasomotion was impaired in our study in the muscle of such rats after acute hyperglycaemia [15,16]. The myogenic response was impaired in non-diabetic, galactosefed rats [17].…”
Section: Functional Changesmentioning
confidence: 63%
“…One has looked at the chronological evolution of the process in insulin-resistant, fructose-fed rats and found that they were first insulin resistant, then endothelium-dependent vasodilatation defects appeared and finally hypertension developed [14]. Precapillary vasomotion was impaired in our study in the muscle of such rats after acute hyperglycaemia [15,16]. The myogenic response was impaired in non-diabetic, galactosefed rats [17].…”
Section: Functional Changesmentioning
confidence: 63%
“…at 5 mmol/l [18]) instead of at isoglycaemia, which resulted in slightly higher glucose levels during insulin than during saline infusion. It is not clear whether this difference affected our results, but because hyperglycaemia impairs microvascular function [47,48], we may, if anything, have somewhat underestimated insulin-mediated effects on microvascular function.…”
Section: Discussionmentioning
confidence: 86%
“…While the vasodilating effects of insulin are established [9,10], the direct vascular actions of short-term hyperglycaemia are largely unknown. Studies investigating the effects of high glucose on macrovascular and microvascular perfusion have yielded conflicting results: some have shown attenuated vasodilation [11,12,13,14,15,16], some have demonstrated enhanced vasodilation [17,18,19,20], whereas others found no changes in vascular tone [21,22,23]. The present study was designed to gain deeper insights into the immediate effects of high glucose on endothelial NO formation and vascular tone, and its stimulatory role on the vascular effects of insulin.…”
Section: Introductionmentioning
confidence: 96%